Systematic Literature Review: Membangun Kesejahteraan Sosial Indonesia, Peluang dan Hambatan - Triono, Tomi Agus (Journal of Society Bridge, 2024)
This study aims to explore the opportunities and challenges in building social welfare in Indonesia through a systematic review of relevant prior literature. Utilizing the systematic literature review (SLR) method, 20 high-quality studies were identified, evaluated, and synthesized to generate significant findings. The results reveal potential opportunities, such as stable economic growth, policy reforms, the utilization of digital technology, and partnerships with civil society organizations and the private sector. However, challenges that need to be addressed include budget constraints, regional disparities in access to basic services, lack of capacity and coordination among government agencies, and geographical and demographic challenges. These findings provide a comprehensive overview of the supporting and hindering factors in building social welfare in Indonesia, which can serve as a basis for developing more effective policies and strategies. To optimize opportunities and overcome challenges, strong commitment and collaboration from all stakeholders are required, along with specific efforts such as increasing budget allocation, strengthening coordination, adopting technology and innovation, and prioritizing development in underdeveloped areas. With coordinated and sustained efforts, Indonesia can achieve equitable and inclusive social welfare for all its citizens.